Diretrizes para reciclagem do RCD gerado no município de Farroupilha como agregado na pavimentação de vias rurais - Pizoni, Eduardo (Universidade do Vale do Rio dos Sinos, 2019)
The significant amount of waste generated by the construction sector (construction and demolition waste - RCD) is now a major environmental problem to be faced by the construction companies and by the public authorities, requiring efforts by the municipalities with a focus on the management and reuse of the material. What is verified, however, is that in practice the public power itself in many cases does not recycle the waste, being recycled in the aggregate provided for by law, prioritizing the consumption of the natural aggregate. In this context, this master's dissertation presents guidelines for adapting the municipal crusher for recycling RCD in aggregate, with a view to the use of paving in rural roads. Among the stages of the study, the amount of "Class A" construction and demolition waste generated in the municipality was estimated, the amount of natural aggregate used in the primary coating of the pavements in the rural area, and the evaluation of the guidelines for the implementation of the recycling plant RCD in the municipal crusher, evaluation of measures and costs necessary to adapt the site. Finally, a survey was carried out of the costs of producing the natural and recycled aggregate. As main results, the work presents the consumption of natural aggregate used, as well as the volume of RCD generated in the municipality, besides the costs for adaptation of the municipal crusher and comparison of the production values of each aggregate. With the analysis of the results obtained, one can compare the replacement of the natural aggregate by the recycled aggregate in paving, where a natural aggregate saving of 68,42% was obtained. In relation to the unit cost of the recycled aggregate, a reduction of 14,08% was obtained in comparison to the unit cost of the natural aggregate.
Keywords: Resíduos de construção e demolição; Agregado natural; Britador; Usina de reciclagem; Construction and demolition waste; Natural aggregate; Crusher; Recycling plant; ACCNPQ::Engenharias::Engenharia Civil